INFLUENCE OF OXIDATION DEGREE ON ANTIWEAR PROPERTIES AVIATION OILS - Mikosianchyk, Oksana; Yakobchuk, Oleksandr; Pedan, Yevhen; Berezivskyi, Nazarii (Problems of Friction and Wear, 2023)
Control of the quality of lubricants both in product batches and in the process of operation is an important stage in the maintenance of aviation equipment since the assessment of the physicochemical composition of lubricants and their tribotechnical parameters allows for determining the correct oil and lubricant replacement interval. An analysis of the influence of the intensity of oxidation of aviation oil for axial hinges of helicopter propeller bushings on oil’s anti-wear characteristics was made. An increase in temperature to 120 ºC leads to the intensification of oxidation processes. The consequences of oxidation are the increased viscosity of oils due to the polymerization of molecules of the oxidized base of lubricants, the formation of organic acids, lacquer and deposits, as well as the exhaustion of most oil additives. An increase in the kinematic viscosity of aviation oils with a duration of oxidation of 96 hours by 0.7...2.12 mm2/s was established, depending on the package of multifunctional additives to the basic base. The assessment of the increase in the acid number of aviation oils and the formation of resins during the determination of stability against oxidation was made - with a duration of oxidation of 96 hours, the rate of formation of oxidation products depends on the package of multifunctional additives. The change in the micro hardness of the metal surface layers at the increase in the oil acid number was analysed and the weakening mechanisms were determined. The growth of steel wear due to the weakening of the metal surface layers due to the plasticizing effect of oxidation products that are formed during thermomechanical activation in the friction process has been established. During friction, the activated surface of the metal acts as an oxidation catalyst. It is justified to reduce the periodicity of lubricant material quality control during operation, which will ensure increased wear resistance of elements of triboconjugation.